Effects of Facebook Fan Pages on Consumer Brand Loyalty and Purchase Intention - Yi-Fen Chen; Wan-Hsin Yen; Tzu-I Jou (SAGE Open)
As companies began to leverage Facebook, a series of marketing battles ensued. Facebook’s growing popularity has made social media an essential tool in internet marketing. This study examines how interactive features of Facebook fan pages influence consumers’ brand loyalty and purchase intentions. It considers key factors such as sense of belonging, interactivity, word-of-mouth, information value, brand community identification, and trust. Data were collected through an online survey of 468 Facebook users. The study proposes a novel framework explaining how brand community identification, trust, and loyalty influence purchase intention. It provides empirical insights into mechanisms that drive engagement and loyalty within social media brand communities. Structural equation modeling assessed the correlations among variables. The findings show that sense of belonging and interactivity significantly contribute to brand community identification. Positive word-of-mouth and information value strongly enhance trust. In turn, identification positively influences trust. Both identification and trust directly increase loyalty. Additionally, loyalty significantly affects consumers’ purchase intentions. This study expands auction theory’s application to marketing by using it to explain consumer behavior in social media environments. It makes a valuable theoretical contribution by aligning economic mechanisms with social interactions in online brand communities. The findings offer practical value for firms seeking to strengthen their social media presence. Businesses can use these insights to improve customer relationships, boost engagement, and attract new audiences. By focusing on community factors like belonging, interactivity, information sharing, and trust, firms can design more effective fan page strategies to foster loyalty and drive purchase behavior.